Adverse Effects of Plasticizers and Pesticides on Female Reproductive Health. Issue 1 (January 2022) - Ramakrishna, Manjunath Paidakula; Prasad, Rashmi Mahadev; Huchegowda, Srinivas; Ramanna, Manasa; Sharma, Manoj Kumar; Huchegowda, Ravish
Central neuroendocrine system regulated by hypothalamus, controls most of the body homeostasis involving processes, like metabolism, reproduction, stress responsiveness, growth, and energy balance mainly through hormonal signals. Plasticizers and pesticides interact as endocrine disruptors with endocrine hormones causing adverse effects which tend to destroy the body homeostasis. Exposures to these compounds during critical developmental stages such as puberty and pregnancy (prenatal or perinatal) influence neurodevelopment, social behavior of the growing fetus and causes sexual dimorphism. Plasticizers and pesticides systemize its effects on adulthood either by mimicking, antagonizing, or having an impact on steroidal activity also along with hormonal disruptions. The aim of this review is to address some of the effects of plasticizers and pesticides exposure on female behavior. In this review, we are discussing the remedial nutritional choice to control the plasticizers and pesticides mediated endocrine disruption.